Implementasi Undang-Undang Desa Pasca Revisi: Tantangan dan Prospek - Ian Aji HermawanIan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the urgency of revising Law Number 6 of 2014 on Villages, which was amended through Law Number 3 of 2024, and its impact on village governance in Indonesia. The research focuses on comparing legal substance before and after the revision, identifying implementation problems, and reinforcing decentralization theory as a foundation for participatory and sustainable village governance. The findings reveal that the Village Law revision is a crucial step in addressing previous weaknesses, particularly in oversight, accountability in the use of village funds, gender inclusion, and the integration of technology in governance. However, several issues remain post-revision, such as limited understanding among village officials, unclear technical regulations, and insufficient community participation. This study recommends the need for extensive training for village officials, comprehensive derivative regulations, and stronger public involvement in oversight. These findings support previous literature that emphasizes the importance of structural readiness and institutional support in decentralization implementation. This research is expected to contribute academically to village policy evaluation and promote public policy reform grounded in local wisdom and participatory principles.